An Influence of Immunomodulation on Th1 and Th2 Immune Response in Endometriosis in an Animal Model. (5th November 2013) - Szymanowski, K.; Niepsuj-Biniaś, J.; Dera-Szymanowska, A.; Wołuń-Cholewa, M.; Yantczenko, A.; Florek, E.; Opala, T.; Murawski, M.; Wiktorowicz, K.
Abstract : Aim. To assess the role of the Th1 and Th2 cellular response in the etiology of endometriosis observed in a rat model, with the use of the RESAN immunomodulator. Materials and Methods. A comparative analysis of cytokines in blood serum typical of Th1 (TNF- α and INF- γ ) and Th2 (IL-4, IL-6, IL-10) cell response in groups of rats, in which RESAN preparation was used as prophylaxis (Gr. I) or treatment (Gr. II) of endometriosis. Results. The results indicated an increase in the level of cytokines in blood serum typical of Th2 cell response by comparing the second and third stages of the experiment in the second group of rats and a decrease in IL-4 and IL-10 between III and IV stages. There was a significant difference in cytokine levels during the third stage of the experiment by comparing I and II groups of rats. In the III group of rats, levels of IL-10 significantly increased between the II and III stages of the experiment. Conclusion. RESAN preparation shows Th2 cell response, inhibiting the development of endometriosis in a rat model. Due to successful prophylactic action, one may speculate that RESAN vaccine may be effective as a complementary treatment after surgical excision.